Event Internasional sebagai Sarana Marketing dan Branding UMKM (Studi pada UMKM Kopi Tjolo Kudus) - Rahmatillah, Ja’sy Zhilaal; Karsono, Lorena Dara Putri (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2024)
This research aims to determine the driving factors, marketing efforts carried out, and the impact both in terms of marketing and branding in utilizing international marketing events at the G20 event for Tjolo Coffee MSMEs. This type of research approach uses qualitative research. The data collection method was carried out by interviewing various internal and external parties from the research object, and documentation. The results of this research show that Tjolo Coffee MSMEs are encouraged to take part in marketing events in the G20 due to factors from the MSMEs themselves and the support from the government. In order for marketing to run optimally, UMKM Kopi Tjolo applies marketing methods such as setting up stands, testers, flyers and business cards. Meanwhile, for product branding purposes, UMKM Kopi Tjolo applies several methods, namely adding the G20 logo to Kopi Tjolo's social media such as on the Website, Instagram, Facebook, WhatsApp and Tik-tok, as well as on employee uniforms, as well as sharing experiences from participating in the marketing of the G20 event in Bali into their social media accounts, and changed the packaging to cans to match export standards. The impact felt after these efforts can expand marketing and improve its image. However, another fact was discovered that from an international perspective it has not had much of an impact